(3MGTjI Ydi LGeY GdaUhdjjfs - (3eLghds; (3HOQ GdOjf eMehO Hf GSQGFjd GdTgjQ HGHf bGVj SeGhfI,J (B823 (3g` s
(3ChdgG (B:s
(3hHYO agPg MhGT LQOJgG ef NW CSJGPi hhGdOi NGJeI GdeMbbjf Rjf GHf HNjQ GdMfai Ydi cJGH LGeY GdaUhdjf GdaUd GdChd bhdg Cbhd LYd CUMGHfG HefRdI GdUMGHi s
(3BNQgG (B:s
(3Cbhd bO jWdH eGdjS dg adGHO ef GdJUQjM HGdbHV adGjfHZi GdJbjjO HRQGYI GdeSJCLQ gPG GNQg hGddg GYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3djOf (B(2000) s
Keywords: (3CUhd Gdabgs